Using the right tool for the right situation: tailoring remediation plans for problem trainees within accredited marriage and family therapy programs - McDaniel, Kara Z. (Kansas State University, 2007)
Within the field of medicine and clinical/counseling psychology, there has been an overabundance of research and literature devoted to specific areas of focus such as trainee impairment, remediation, and dismissal procedures. Although literature does exist in relation to the specific types of remediation methods being used by graduate training programs, no research to date, however, has addressed what types of remediation methods would be most effective in response to the various types of impairment experienced by therapists-in-training (Russell & Peterson, 2003; Forrest et al., 1997). Using a modified version of the Delphi method, the present study seeks to bridge this existing gap by exploring the types of remediation methods deemed most effective for the specific types of impairment experienced by trainees within master’s and doctoral level accredited Marriage and Family Therapy graduate training programs. The purpose of the study was to answer the following questions: 1. What, given a list of impairments and remediation methods would, supervisors and/or professors within MFT graduate training programs list as the most effective type of remediation method for a specific type of impairment? 2. Given the initial answers of experts, once they are provided the answers from their colleagues, can they come to a greater consensus about the most effective remediation methods for specific types of impairment? Those remediation methods chosen by panelists that had a median of 6.00 to 7.00 and interquartile range of 0.00 to 1.50 made the final profile. Results indicated that, given the initial answers of experts, the panel of experts was able to reach a greater consensus about which types of remediation methods they deemed most effective in responding to the corresponding types of impairment. Furthermore, during the first phase of questioning, the panel of experts also generated relevant commentaries with regard to responding to student impairment. Finally, limitations and directions for future research are discussed.
Keywords: Remediation Plans; Student Remediation; Remediation; Impairment; Student Impairment; Problem Trainees; Psychology, General (0621)